A review of studies on specialized learner corpora. - Deviy, Sharmilah; Mohamad Ali, Afida; Chan, Mei Yuit; Muhammad Saliluddin, Suhainizam; Amin Nordin, Syafinaz; Hod, Rafidah; Mohd Sharef, Nurfadhlina; Mohamad Ali, Afiza (Kansai University, 2020)
Recent years have shown a significant growth in learner corpora in the area of English for Specific Purposes (ESP), specifically in the academic and professional context. For studies in English for Academic Purposes (EAP), analysis on learner corpora mainly focused on aspects of form and function in academic genres. This paper reviews 192 learner corpora to determine their availability and usage according to the two main branches of ESP field: EAP and EOP/EPP (English for Occupational Purposes/ English for Professional Purposes). It also identifies inaccessible learner corpora on the online platforms. The review concludes that EAP has been the prime focus in the field of learner corpus studies compared to EOP/EPP. Additionally, only a handful of specialized and professional genre-related learner corpora can be found whereas academic ones are more common. This review establishes the importance of EOP/EPP learner corpora as one of the ways to increase the genre competence of learners and practitioners of specialized discourses.